Pembelajaran Mitigasi Bencana di Sekolah Dasar dengan Metode Demonstrasi - Wita Salwa Salsabila; Rachmah Rafa Dinda (Proceedings Series on Social Sciences & Humanities, 2021)
Geographically Indonesia is an island nation and has a greater sea area than land and is at the confluence of three plates namely, the Pacific plate, indoaustralis and also Eurasia. This makes indonesia as one of the countries that are often hit by disasters. Disaster mitigation education based on local wisdom is conducted in the 2013 curriculum by (1) identifying local wisdom in disaster mitigation, (2) integrating in learning. With the understanding of disaster mitigation is expected to be the basis for learners to be able to take action to reduce the influence of a hazard before the danger occurs. And it can also be one of the solutions that can be done in Indonesia to reduce the impact of disasters that can result in accidents and even deaths. This research aims to develop disaster mitigation models in elementary schools. The results of disaster education research is one of the solutions in schools to reduce the impact of disasters, as well as familiarize students to be responsive and ready for disasters. Therefore, disaster learning model needs to be developed assuming that the focus of mitigation now is not about disaster management, but refers to the understanding of responsiveness. Disaster learning should be provided through a demonstration model that can involve cognitive, affective, and psychomotor spheres in the framework of disaster mitigation.